Rain over Baghdad An Egyptian Novel. - El Badry, Hala (The American University in Cairo Press, 2014)
What was it like to live in Iraq before the earth-shaking events of the end of the twentieth century? The mid-seventies to the late eighties witnessed Saddam Hussein's rise to power, the establishment of Kurdish autonomy in the north, and the Iraq-Iran war. It also brought an influx of oil wealth and a parallel influx of Arab talent, including many Egyptians. The narrator has a behind-the-scenes view of what was really happening at a critical juncture in the history of the region. Moreover, she has a mystery to solve: an Iraqi woman, a communist journalist, has disappeared...